Mast cell-derived interleukin-4 mediates activation of dendritic cell during toll-like receptor 2-mediated inflammation - Friedel, Joschua; Pierre, Sandra; Kolbinger, Anja; Schäufele, Tim J.; Aliraj, Blerina; Weigert, Andreas; Scholich, Klaus (Frontiers in Immunology, 2024)
During an innate inflammation, immune cells form distinct pro-and anti-inflammatory regions around pathogen-containing core-regions. Mast cells are localized in an anti-inflammatory microenvironment during the resolution of an innate inflammation, suggesting anti-inflammatory roles of these cells. Here, we investigated mast cell-dependent changes in the regional distribution of immune cells during an inflammation, induced by the toll-like receptor (TLR)-2 agonist zymosan. High-content imaging showed that the distance between the zymosan-containing core-region and the anti-inflammatory region, described by M2-like macrophages, increased in mast cell-deficient mice. Absence of mast cells abolished dendritic cell (DC) activation, as determined by CD86-expression and localized the DCs in greater distance to zymosan particles. The CD86 -DCs had a higher expression of the proinflammatory interleukins (IL)-1 and IL-12/23p40 as compared to activated CD86 + DCs. IL-4 administration restored CD86 expression, cytokine expression profile and localization of the DCs in mast cell-deficient mice. The IL-4 effects were mast cell-specific, since IL-4 reduction by eosinophil depletion did not affect activation of DCs. Taken together, we show that mast cells induce DC activation selectively at the site of inflammation and thereby determine their localization within the inflammation. Overall, mast cells have anti-inflammatory functions in this inflammation model and limit the size of the pro-inflammatory region surrounding the zymosan-containing core region.